5a-6b-a-2b=

Simple and best practice solution for 5a-6b-a-2b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a-6b-a-2b= equation:


Simplifying
5a + -6b + -1a + -2b = 0

Reorder the terms:
5a + -1a + -6b + -2b = 0

Combine like terms: 5a + -1a = 4a
4a + -6b + -2b = 0

Combine like terms: -6b + -2b = -8b
4a + -8b = 0

Solving
4a + -8b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '8b' to each side of the equation.
4a + -8b + 8b = 0 + 8b

Combine like terms: -8b + 8b = 0
4a + 0 = 0 + 8b
4a = 0 + 8b
Remove the zero:
4a = 8b

Divide each side by '4'.
a = 2b

Simplifying
a = 2b

See similar equations:

| 3x+36=15 | | (7x+3)(x-5)=0 | | 33.46=7g+3.92 | | 2-0.375x=13 | | 1.14g-8=0.55 | | (10x+4)+(4x-3)=12x+16 | | e^4x=5 | | 2x=3x^2-5 | | -15=3+2x | | 7n+2=4n+18 | | 817/95 | | 5y/3=15 | | z=2+1.75q | | 13x+14=5x+118 | | 3ab+2a=ab | | 180=7y-4 | | b/5+1/7=19 | | 5x^2+24x-12=0 | | 11-9x=24-16x | | 3/8+8m/7=93/56 | | x-8y=4 | | 4/7s=12 | | b/11-5b/11=16/11 | | 5/3y=15 | | 14x-1/2x5 | | -2(r+9)=-27 | | ((n+1)(n+2)(2n+3))/6 | | x=144p/y | | -10(n+10)=-270 | | 3x+16=180 | | 216-2x=180 | | 4x^2-29x-12=0 |

Equations solver categories